ANALYTICAL DESCRIPTIVE STUDY OF RELIGIOUS ATTITUDE CONSTRUCTION MODEL AT LPTK ORGANIZING PROFESSIONAL POST SM-3T TEACHER EDUCATION IN INDONESIA - Suresman, dkk, Edi (EDUTECH, 2015)
Abstrack, A successful education is influenced by various factors, one of which is method or approach to education to build a religious attitude for students. One of Islamic values-based learning methods that have been implemented at UPI in an effort to build religious attitude of PPG Post SM-3T participants is targhib and tarhib learning model and the results are very effective. The focus of problem in this study is on whether targhib - tarhib model was used in other LPTKs in building religious attitude for PPG Post SM-3T participants?The purpose of this study is to understand what learning model is applied in LPTK organizing PPG Post SM-3T in building religious attitude for PPG participants?This study was conducted by using a descriptive approach, qualitative-interpretative. The techniques of data collection used are questionnaire in the form of religious attitude distributed to PPG Post SM-3T participants, religious builder in a dormitory, and manager, and participation observation in the field. The data analysis was performed in five steps: verification of the data, presentation of the serial number for answer sheets, scoring of answer sheet, calculation of religious attitude trends by estimating the population and its percentage, and analysis of trends to differences in the effectiveness of each method used to mold religious attitude in each of LPTK organizing PPG.The results of the study suggest any variation of models used in each of LPTK, i.e., lectures, tutorials, thariqah shufis and targhibs - tarhibs. The targhib - tarhib have the most successful position than other models. Targhib – tarhib are 84%, lectures, 50%, shufis, 80%, tutorials, 70%. Keywords: Construction Model, Religious Attitude, PPG Post SM-3T. Abstrak, Keberhasilan pendidikan dipengaruhi oleh berbagai faktor, salah satu faktor tersebut adalah metode atau pendekatan pendidikan yang dapat membangun sikap religius bagi peserta didik. Salah satu metode pembelajaran berbasis nilai-nilai Islam yang sudah diimplementasikan di UPI dalam upaya membangun sikap religius peserta PPG Pasca SM-3T yaitu model pembelajaran targhib dan tarhib dan hasilnya sangat efektif. Fokus permasalahan dalam penelitian ini adalah apakah model targhib – tarhib digunakan di LPTK lain dalam pembinaan sikap religius bagi peserta PPG Pasca SM-3T?Tujuan penelitian ini adalah ingin mengetahui model pembelajaran seperti apa yang diterapkan LPTK penyelenggara PPG Pasca SM-3T dalam pembinaan sikap religius bagi peserta PPG?Penelitian ini menggunakan pendekatan deskriptif, kualitatif-interpretatif. Teknik pengumpulan data digunakan angket berupa sikap religius yang disebar kepada para peserta PPG Pasca SM-3T, pembina keagamaan di asrama, pengelola asrama juga melalui observasi partisipasi di lapangan. Analisis data dilakukan dengan lima langkah berikut, yaitu verifikasi data, pemberian nomor urut lembar jawaban, penyekoran lembar jawaban, menghitung kecenderungan sikap religius dengan menaksir terhadap populasi dan prosentasenya, serta menganalisis kecenderungan perbedaan efektivitas dari masing-masing metode yang digunakan untuk membentuk sikap religius di setiap LPTK penyelenggara PPG.Hasil penelitian menunjukkan adanya variatif model yang digunakan di masing – masing LPTK, yaitu model kuliah, model tutorial, model thariqah shufi dan model targhib – tarhib. Dan model targhib – tarhib menempati posisi yang paling berhasil dibanding model lainnya. Targhib – tarhib 84%, model kuliah 50%, model shufi 80%, model tutorial 70%.Kata kunci : Model Pembinaan, Sikap Religius, PPG Pasca SM-3T.